Neurobiologie úzkostných poruch - Praško, Ján; Končelíková, Dana; Grambal, Aleš; Látalová, Klára (Psychiatrie (Praha, Print), 2013)
Fear and anxiety are complex behaviors that represent responses to environmental threats. There is a different between these two behaviors, fear is a response to a real or clearly identifiable threat and functions to remove the individual from a harmful situation. In contrast, anxiety is a preparation response for future possible danger and often proceeds in the absence of a truly threatening stimulus. Our current understanding of the neurobiology of fear and anxiety centers lar- gely on three interrelated systems: the amygdala, the HPA (hypothalamic–pituitary–adrenal gland) axis, and neuromodulators (e.g., serotonin). Fear and anxiety stimuli selectively activated serotonergic neurons in the dorsal raphe nucleus, which then project into the amygdala and the hypothalamic portion of the HPA axis. Combining functional imaging with genomic analysis, researchers have associated a short allele of the promoter (5-HTTLPR) for the human serotonin transporter gene (SLC6A4) with anxiety-related personality traits, for example, fear condition-ability. Individuals carrying one or two copies of the truncated version of SLC6A4 exhibit reduced serotonin signaling and, intere- stingly, greater amygdala aktivity and higher anxiety during exposure. Thera are also few morfological findings, attention is directed toward the medial prefrontal cortex (mPFC) and the interaction it has with the amygdala as this circuit has crucial roles in both the acquisition and the extinction of fear associations. Recent findings on rodents and nonhuman primates report that modifying plasticity in the mPFC alters fear and affects extinction, suggesting that targeting plasticity in the mPFC could constitute a therapeutic tool for the treatment of anxiety disorders.